Laser surface treatment-introduced gradient nanostructured TiZrHfTaNb refractory high-entropy alloy with significantly enhanced wear resistance. (30th May 2022) - Luo, Jiasi; Sun, Wanting; Duan, Ranxi; Yang, Wenqing; Chan, K.C.; Ren, Fuzeng; Yang, Xu-Sheng
Highlights: Gradient nanostructured layer on TiZrHfTaNb refractory high-entropy alloy was fabricated by laser surface remelting technique. The average grain size in gradient nanostructured layer is refined from ∼ 200 µm in matrix to only ∼ 8 nm in the top surface. The microhardness is increased from ∼ 240 HV in matrix to ∼ 650 HV in the top surface layer. The decomposition-mediated gradient refinement mechanisms were revealed mainly by HRTEM. The gradient nanostructure shows significantly enhanced wear resistance, reducing the wear rate with an order of magnitude. Abstract: Heterogeneous gradient nanostructured metals have been shown to achieve the strength-ductility synergy, thus potentially possessing the enhanced tribological performance in comparison with their homogeneous nanograined counterparts. In this work, a facile laser surface remelting-based surface treatment technique is developed to fabricate a gradient nanostructured layer on a TiZrHfTaNb refractory high-entropy alloy. The characterization of the microstructural evolution along the depth direction from the matrix to the topmost surface layer shows that the average grain size in the ∼100 µm-thick gradient nanostructured layer is dramatically refined from the original ∼200 µm to only ∼8 nm in the top surface layer. The microhardness is therefore gradually increased from ∼240 HV in matrix to ∼650 HV in the topmost surface layer, approximately 2.7 times. Noticeably, the original coarse-grained single-phase body-centered-cubic TiZrHfTaNb refractory high-entropy alloy is gradually decomposed into TiNb-rich body-centered-cubic phase, TaNb-rich body-centered-cubic phase, ZrHf-rich hexagonal-close-packed phase and TiZrHf-rich face-centered-cubic phase with gradient distribution in grain size along the depth direction during the gradient refinement process. As a result, the novel laser surface treatment-introduced gradient nanostructured TiZrHfTaNb refractory high-entropy alloy demonstrates the significantly improved wear resistance, with the wear rate reducing markedly by an order of magnitude, as compared with the as-cast one. The decomposed multi-phases and gradient nanostructures should account for the enhanced wear resistance. Our findings provide new insights into the refinement mechanisms of the laser-treated refractory high-entropy alloys and broaden their potential applications via heterogeneous gradient nanostructure engineering.